Manajemen Strategi Dalam Mempertahankan Eksistensi Pondok Pesantren Nurul Islam Sribandung - Oktavia Anggraini; Achmad Syarifuddin; Manalullaili Manalullaili (Social Science and Contemporary Issues Journal, 2023)
This research is entitled "Strategic Management in Maintaining the Existence of Nurul Islam Seribandung Islamic Boarding School". This study aims to determine the efforts of the Nurul Islam Seribandung Islamic boarding school and the strategic management carried out to maintain its existence. This research is a qualitative research type with a descriptive approach. The data sources in this study are primary data sources and secondary data. Data collection techniques by interview, observation and documentation. The results of this study indicate that the efforts made in maintaining the existence of the Nurul Islam Seribandung Islamic boarding school are by maintaining the existing traditions at the Islamic boarding school then by recruiting human resources and building good relations with alumni, the community and also the government. The Nurul Islam Seribandung Islamic boarding school has implemented a fairly good management strategy. Although there are several challenges faced in carrying out its strategy such as insufficient human resources, constrained funding sources, and inadequate facilities and infrastructure. So that causes this Islamic boarding school to experience a decrease in the number of students. But even so, The Nurul Islam Seribandung Islamic boarding school still stands as an Islamic educational institution that is known by the public. Keywords: Strategic Management, Existence, Islamic Boarding Schools